Structural Characterization of Campylobacter jejuni Lipooligosaccharide Outer Cores Associated with Guillain-Barré and Miller Fisher Syndromes - Godschalk, Peggy C. R. (American Society for Microbiology, 2007)
Molecular mimicry between lipooligosaccharides (LOS) of Campylobacter jejuni and gangliosides in peripheral nerves plays a crucial role in the pathogenesis of C. jejuni-related Guillain-Barré syndrome (GBS). We have analyzed the LOS outer core structures of 26 C. jejuni strains associated with GBS and its variant, Miller Fisher syndrome (MFS), by capillary electrophoresis coupled with electrospray ionization mass spectrometry. Sixteen out of 22 (73%) GBS-associated and all 4 (100%) MFS-associated strains expressed LOS with ganglioside mimics. GM1a was the most prevalent ganglioside mimic in GBS-associated strains (10/22, 45%), and in eight of these strains, GM1a was found in combination with GD1a mimics. All seven strains isolated from patients with ophthalmoplegia (GBS or MFS) expressed disialylated (GD3 or GD1c) mimics. Three out of 22 GBS-associated strains (14%) did not express sialylated ganglioside mimics because their LOS locus lacked the genes necessary for sialylation. Three other strains (14%) did not express ganglioside mimics because of frameshift mutations in either the cstII sialyltransferase gene or the cgtB galactosyltransferase gene. It is not possible to determine if these mutations were already present during C. jejuni infection. This is the first report in which mass spectrometry combined with DNA sequence data were used to infer the LOS outer core structures of a large number of neuropathy-associated C. jejuni strains. We conclude that molecular mimicry between gangliosides and C. jejuni LOS is the presumable pathogenic mechanism in most cases of C. jejuni-related GBS. However, our findings suggest that in some cases, other mechanisms may play a role. Further examination of the disease etiology in these patients is mandatory.